The American Southwest as Muse: Maggi Payne's Sonic Desertscapes. Issue 3 (3rd May 2016) - Feisst, Sabine
Abstract : Deserts have long captivated the imagination of musicians. Ferde Grofé, Edgard Varèse, Olivier Messiaen, and Steve Reich among others created compositions reflecting desert landscapes. Most of them, however, have had little familiarity with these places. David Dunn, Richard Lerman, and Maggi Payne, on the other hand, have developed strong connections with deserts and portrayed them in numerous works, compelling examples of sensitive engagement with Southwestern landscapes. This paper centres on Payne, one of few women composers whose music often features deserts in California, Nevada, New Mexico, and Utah. Three works, Airwaves (realities), Desertscapes, and Apparent Horizon, will be analysed and contextualised against the background of Payne's environmental philosophies.